Analisis Ketimpangan Produktivitas dan Dualisme Ketenagakerjaan di Kabupaten Probolinggo - Afton Ilman Huda; Multazem .; Husni Mubarok (CV. ITTC INDONESIA, 2026)
Productivity inequality and labor dualism remain structural problems commonly found in developing regions, including Probolinggo Regency. This condition is characterized by disparities in productivity levels between the formal and informal sectors, as well as imbalances in labor quality and welfare. This study aims to analyze the extent of productivity inequality and examine the forms of labor dualism occurring in Probolinggo Regency. The research employs a qualitative descriptive approach using secondary data obtained from the Central Statistics Agency (BPS), local government reports, and relevant literature. Data analysis is conducted through comparative and interpretative analysis of employment structures and sectoral productivity. The findings indicate a significant productivity gap between the formal and informal sectors, where the informal sector absorbs the majority of the workforce but exhibits relatively low productivity levels. This labor dualism contributes to low income levels and limited job security for informal workers. The study highlights the importance of policy interventions aimed at improving labor quality and productivity to reduce employment inequality.